The effect of quality of work life and organizational citizenship behavior on employee performance: Mediated by work motivation - Royan, Muhammad; Assa, Adrie Frans (Global Academy of Business Studies, 2025)
Purpose: This study aims to analyze the direct and indirect effects of Quality of Work Life (QWL) and Organizational Citizenship Behavior (OCB) on employee performance, with work motivation as a mediating variable within the manufacturing industry context. Methodology: A quantitative approach was used involving 150 permanent employees of PT Garuda Metalindo. Data were collected using a 1–5 Likert-scale questionnaire and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique through SmartPLS 4. The measurement model, structural model, and mediation effects were evaluated to determine significance and explanatory power. Result: Findings show that QWL and OCB have positive and significant effects on employee performance. Both variables also significantly influence work motivation, which in turn positively affects performance. Work motivation partially mediates the influence of QWL and OCB on employee performance. The model explains 55.4% of employee performance variance and 71.9% of work motivation variance. Conclusion: Improving QWL and OCB directly enhances employee performance and indirectly strengthens performance through increased work motivation. These results confirm the importance of supportive work environments and voluntary employee behavior in improving organizational outcomes. Limitation: This study is limited to one manufacturing company and uses cross-sectional data, which may restrict generalizability and causal interpretation. Contribution: This research contributes by validating the mediating role of work motivation in the relationships between QWL, OCB, and performance, offering empirical insights for HR practitioners and manufacturing organizations to design strategies that improve employee motivation and performance.